ANALISIS PEMANFAATAN ASET DESA (STUDI PADA DESA DUKUH, KECAMATAN NGADILUWIH KABUPATEN KEDIRI) - FRIYANTO; YOSAR HARITSAR (AKADEMIKA, 2023)
This research appoint on public sector accounting (village government), that focusing on village assets management. The purpose of this research to understand and analyze the management of village assets, the regulations used as guidelines, and the problems that are currently occur. This research was located at Dukuh Village, Ngadiluwih Regency, Kediri District. This type of research uses descriptive qualitative. Data collecting techniques using observation, interview, dan documentation. Methods of data analysis using interactive models (data reduction, data display, and conclusion drawing). The results of the research and discussion explain that basically some of the assets management at Dukuh Village has been applied according the guidelines of Peraturan Menteri Dalam Negeri Nomor 1 Tahun 2016, and the rest still having problems. The outline of the problems of village assets management at Dukuh Village are the limit of human resources, the limit of budget, and lack socialization from the authorities.